Odpowiedzi

Najlepsza Odpowiedź!
2009-11-21T15:11:33+01:00
3×(×-6y)-2y(×+7y)=3x²-18xy-2xy-14y²=3x²-20xy-14y²
b)(5-×)×+4(×-3)-6×(0,3×+0,5)= 5x-x²+4x-12-1,8x²-3x=6x-2,8x²-12
c)(×-1)²-(×+2)²=x²-2x+1-(x²+2x+4)=x²-2x+1-x²-4x-4=-6x-3
d)3(×+2)²-8(×-2)²+(×+2)(×-2)=3(x²+4x+4)-8(x²-4x+4)+x²-4=
=3x²+12x+12-8x²+32x-32+x²-4=-4x²+44x-24
2009-11-21T15:14:27+01:00
Zapisz wyrazenie w jak najprostszej postaci
3×(×-6y)-2y(×+7y)=3x²-18xy-2yx-14y²=3x²-20xy-14y²
b)(5-×)×+4(×-3)-6×(0,3×+0,5)=5x-x²+x-12-1,8x²+3x=-2,8x²+9x-13
c)(×-1)²-(×+2)²=x²-2x+1-x²-4x-4=-6x-3
d)3(×+2)²-8(×-2)²+(×+2)(×-2) =3x²+12x+12-8x²+32x-32+x²-4=-4x²+44x-24
2009-11-21T15:20:26+01:00
A)3x²-18xy-2xy-14y²=3x²-20xy-14y²
b)5x-x²+4x-12-1,8x²-3x=6x-2,8x²-12
c)(x²-2x+1-x²+4)²=(5-2x)²=25-20x+4x²
d)3(x²+4x+4)-8(x²-4x+4)+x²-4=3x²+12x+12-8x²+32x-32+x²-4=44x-4x²-20